2000
DOI: 10.1023/a:1006405512579
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Combined treatment with interferon-beta, MCNU (Ranimustine), and radiotherapy was assessed in patients with malignant glioma who had not received previous cytotoxic drug therapy. Forty-three patients up to 75 years old with histopathologically confirmed malignant glioma were studied. All patients had tumors measurable by neuroimaging, a Karnofsky performance score exceeding 40, and an expected survival exceeding 2 months. A response rate of 49% (21/45) was observed, including 6 complete remissions (14%) and 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…1 ). We determined IFN-beta dosage based on previously published trials, including a Phase I trial [ 11 , 14 , 17 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). We determined IFN-beta dosage based on previously published trials, including a Phase I trial [ 11 , 14 , 17 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the treatment of malignant gliomas, IFNβ can act as a drug sensitizer, and it enhances the toxicity of chemotherapeutic agents against various neoplasms when administered in combination with nitrosourea [ 10 ]. Combination therapy with IFNβ and nitrosourea has been used primarily in the treatment of gliomas in Japan [ 11 ]. In our previous in vitro study of human glioma cells, we found that IFNβ markedly enhanced chemosensitivity to TMZ [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Type-I interferons (IFNs), specifically IFN-α and IFN-β, exhibit important antineoplastic properties in vitro and in vivo against a wide variety of malignancies ( 4 , 5 ). There has been some evidence for Type-I IFN antitumor activity in GBM in vitro and in vivo , but this primarily involves studies of IFN combinations with chemotherapeutic agents ( 6 ). IFNβ treatment has been shown to sensitize human glioma cells to temozolomide (TMZ) treatment in vitro ( 7 ), and in some cases may have a beneficial therapeutic effect when incorporated in the therapeutic regimen of GBM patients ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the treatment of malignant gliomas, IFN- β can act as a drug sensitizer by enhancing the toxicity of chemotherapeutic agents against various neoplasms when administered in combination with nitrosoureas. Combination therapy with IFN- β and nitrosoureas is primarily used for the treatment of gliomas in Japan [23]. In a previous in vitro study in human glioma cells, we found that IFN- β markedly enhances chemosensitivity to TMZ [24]; this finding suggests that one of the major mechanisms by which IFN- β enhances chemosensitivity is the downregulation of MGMT transcription via p53 induction.…”
Section: Overcoming Alkylating Agent Resistance Due To Mgmtmentioning
confidence: 96%